Identification of recombinant human EPO variants in greyhound plasma and urine by ELISA, LC‐MS/MS and western blotting: a comparative study. Issue 2 (19th August 2015) - Timms, Mark; Steel, Rohan; Vine, John
Abstract : The recombinant human erythropoietins epoetin alfa (Eprex®), darbepoetin (Aranesp®) and methoxy polyethylene glycol‐epoetin beta (Mircera®) were administered to greyhounds for 7, 10 and 14 days respectively. Blood and urine samples were collected and analysed for erythropoietin by ELISA, LC‐MS/MS and western blotting. Limits of confirmation in plasma for western blotting and LC‐MS/MS methods ranged from a low of 2.5mIU/mL, and closely matched the sensitivity of ELISA screening. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Epoetin alfa, darbopoietin and pegylated Epoetin beta were administered to greyhounds and recombinant human EPO detected in plasma and urine samples by ELISA, LC‐MS/MS and western blotting.